The use of volatile anesthetic agents for long-term critical care sedation (VALTS): study protocol for a pilot randomized controlled trial. Issue 1 (December 2015) - Jerath, Angela; Ferguson, Niall; Steel, Andrew; Wijeysundera, Duminda; Macdonald, John; Wasowicz, Marcin
Abstract Background Sedatives are administered to 85 % of intensive care unit (ICU) patients. The most commonly used sedatives are intravenous benzodiazepines and propofol. These agents are associated with over-sedation in 40 to 60 % of patients, which can lead to prolonged intubation, delirium and drug-induced hypotension. Evidence is increasing that volatile anesthetic agents are associated with faster extubation times, improved cardiovascular stability with no end-organ toxicity in comparison to our standard intravenous agents for short-term critical care sedation. Use of volatile agents within the ICU is a novel technique using a specialized delivery and scavenging system, which requires staff training and cultural acceptance. This pilot randomized controlled trial aims to assess the safety and feasibility of delivering volatile agents for long-term patient sedation in the ICU with limited or no experience of this technique. Methods/Design This is a prospective multicenter pragmatic pilot RCT that is blinded to the data analyst. This study aims to recruit 60 adult ICU patients requiring mechanical ventilation and sedation for more than 48 h. Patients will be randomized 2:1 to receive inhaled isoflurane (40 patients) or intravenous midazolam and/or propofol (20 patients) sedation. Sedation is titrated to a targeted Sedation Analgesia Score (SAS) using an explicit sedation-analgesia algorithm until extubation or tracheostomy. Primary safety and feasibility outcomes will assess atmospheric volatile concentration levels and adherence to our sedation-analgesia protocol. Secondary outcomes include time to extubation, duration of ventilation, quality of sedation, delirium, vasoactive drug support, length of stay, serum fluoride levels and mortality. Discussion This pilot project will serve as the basis for a larger RCT that will be powered for important clinical outcomes. Trial Registration ClinicalTrials.gov, NCT01983800 (registration date 2 July 2013).